2019
DOI: 10.1002/cssc.201902590
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Renewable Phthalic Anhydride from 5‐Hydroxymethfurfural by using MoO3/Cu(NO3)2 as Catalyst

Abstract: Herein, a synthetic pathway to renewable phthalic anhydride (PA) from 5‐hydroxymethfurfural (HMF) in one pot is reported. The commonly available catalysts MoO3 and Cu(NO3)2 play a crucial role in integrating the multiple steps of the reaction, namely decarbonylation of HMF to active furyl intermediate (AFI), oxidation of HMF to maleic anhydride (MA), Diels–Alder cycloaddition of AFI and MA, and subsequent dehydration, in one pot. Under mild reaction conditions, a 63.2 % yield of PA is obtained from HMF. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The products of aerobic oxidation of 5‐HMF in water were 2.5 % of DFF, 10.3 % of FDCA, 26.1 % of maleic acid, and 31.5 % of maleic anhydride based on UHPLC‐Q‐Exactive/MS at 92.4 % conversion (Figure S6). The main product from aerobic oxidation of 5‐HMF in water was maleic anhydride, which provided an alternative pathway for producing maleic anhydride based on bio‐platform chemical such as 5‐HMF instead of petroleum‐based raw materials [63] . The mechanism and some parameters on 5‐HMF oxidation in water will be done in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The products of aerobic oxidation of 5‐HMF in water were 2.5 % of DFF, 10.3 % of FDCA, 26.1 % of maleic acid, and 31.5 % of maleic anhydride based on UHPLC‐Q‐Exactive/MS at 92.4 % conversion (Figure S6). The main product from aerobic oxidation of 5‐HMF in water was maleic anhydride, which provided an alternative pathway for producing maleic anhydride based on bio‐platform chemical such as 5‐HMF instead of petroleum‐based raw materials [63] . The mechanism and some parameters on 5‐HMF oxidation in water will be done in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The main product from aerobic oxidation of 5-HMF in water was maleic anhydride, which provided an alternative pathway for producing maleic anhydride based on bio-platform chemical such as 5-HMF instead of petroleum-based raw materials. [63] The mechanism and some parameters on 5-HMF oxidation in water will be done in the future. The total organic carbon (TOC) on PMo 4 V 8 remained larger than 87.1 %, indicating that over-oxidation was occurred to generate CO 2 .…”
Section: Catalytic Activity Of Pmo 4 V 8 /Hap (N)mentioning
confidence: 99%
“…Jia and co-workers have developed a catalytic system based on MoO 3 and Cu(NO 3 ) 2 achieving about 63 % yield using K 2 S 2 O 8 as stoichiometric oxidant. 634,635 The production of biobased PA still needs much research as very few publications are reported for an efficient and competitive chemical route to produce this chemical at large scale. The path reported by Mahmoud and coworkers 633 has the potential to produce high yields of PA but the process is strictly limited by the cost of production of maleic anhydride and furan and the separation, which still needs to be validated.…”
Section: Phtalic Anhydridementioning
confidence: 99%
“…Jia and co-workers have developed a catalytic system based on MoO 3 and Cu(NO 3 ) 2 achieving about 63% yield using K 2 S 2 O 8 as stoichiometric oxidant. 634,635…”
Section: Diesel–alder Reactionsmentioning
confidence: 99%
“… 17 PA obtained renewably form 5-hydroxymethfurfural (HMF) using MoO 3 /Cu(NO 3 ) 2 as a catalyst. 18 Sha group in 2016 designed a conceptual process to prepare PA from corn stover, an agricultural residue. Their techno-economic assessment contends energy integration alternatives as well as water consumption and life cycle greenhouse emissions.…”
Section: Introductionmentioning
confidence: 99%